Monomerization of Phthalocyanines in Water via Their Supramolecular Interactions with Cucurbiturils - Kociscakova, Lucia; Rando, Carola; Kozlikova, Magdalena; Machacek, Miloslav; Novakova, Veronika; Šindelář, Vladimír; Zimcik, Petr (The Journal of organic chemistry, 2023)
Aggregation of phthalocyanines (Pcs) represents a problematic feature that decreases the potential of these macrocycles in a number of applications. In this work, we present a supramolecular approach based on the interaction of aminoadamantyl-substituted Pcs with bulky and hydrophilic cucurbit[7]uril (CB[7]) to increase the levels of Pc monomers in water. A series of zinc(II) Pcs substituted at positions α or β by an aminoadamantyl substituent (with a different level of alkylation of nitrogen) were prepared from the corresponding phthalonitriles. A 1H nuclear magnetic resonance study of the interaction of phthalonitriles with CB[7] in water confirmed the formation of an inclusion complex with an aminoadamantyl moiety with Ka values of ∼1012 M-1. The interaction of CB[7] with Pcs in water substantially weakened H-type aggregation and improved both fluorescence and singlet oxygen production, confirming that this approach is efficient for the monomerization of Pcs. In vitro evaluation of the photodynamic activity of prepared Pcs led to EC50 values in the submicromolar range on HeLa and SK-MEL-28 cells. However, the activity decreased for at least an order of magnitude after host-guest interaction with CB[7] despite better photophysical properties. This was attributed to a much lower uptake by cells due to the very bulky and hydrophilic character of the Pc-CB[7] assembly.